2009
DOI: 10.1583/08-2686.1
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Single-Center Prospective Study of Endovascular Abdominal Aortic Aneurysm Repair With the Talent Stent-Graft

Abstract: Endovascular aneurysm treatment with the Talent stent-graft has proven to be effective in the prevention of AAA rupture into the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 49 publications
1
19
1
2
Order By: Relevance
“…This 30-day outcome in terms of type I endoleak compares well with results recently reported for other EVAR devices [26][27][28][29][30][31]. Even in midterm follow-up, the Endurant stent graft achieved excellent outcomes (1.3% type I endoleak and freedom from type I endoleak of 97%) in patients with a short aortic or severely angulated neck.…”
Section: Discussionsupporting
confidence: 83%
“…This 30-day outcome in terms of type I endoleak compares well with results recently reported for other EVAR devices [26][27][28][29][30][31]. Even in midterm follow-up, the Endurant stent graft achieved excellent outcomes (1.3% type I endoleak and freedom from type I endoleak of 97%) in patients with a short aortic or severely angulated neck.…”
Section: Discussionsupporting
confidence: 83%
“…12,13 Although long-term all-cause mortality is high in the current study, the 30-day mortality data of our cohort are good and even lower than in other series for EVAR and substantially lower than open repair. 1,2,8,12 The EVAR-1 and DREAM trials showed an operative (30-day) mortality rate for the open-repair group of 4.7 and 4.6%, respectively. 1,2 Aneurysm-related death and rupture in our study were limited and at least comparable to results reported in the randomized trials and registries.…”
Section: Discussioncontrasting
confidence: 53%
“…5,12 Through the years, indications for EVAR have changed. In the beginning, EVAR was more likely to be used as a therapy in patients who were unfit for open surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type II endoleaks occur in about 5% to 10% of patients who are treated by EVAR. 2,3 An aggressive approach was adopted in the early days of EVAR, and all type II endoleaks were treated in fear of aneurysm rupture. 4 Most large series assessing type II endoleaks have demonstrated a relationship between persistent type II endoleaks and aneurysm sac expansion, reinterventions, and even rupture.…”
mentioning
confidence: 99%